Identifikasi Gangguan Kepribadian Dramatis Menggunakan Metode Learning Vector Quantization (LVQ) - M Kevin Pahlevi; Budi Darma Setiawan; Tri Afirianto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Personality disorder is one of the health problems experienced and felt by the community. Group B or so-called dramatic is more common due to increased suicide rates, high social media access, still happening brawl and bullying all over, then many phenomena about people who want to steal attention with a physical look or style of language that is not commonly, this can increase the risk of people affected personality disorders, especially the dramatic group. This study try to identify dramatic personality disorders. This dramatic personality disorder is divided into 4 classes. The method used is Learning Vector Quantization. Data obtained from questionnaires using 32 parameters and managed to get data as much as 90 data. This research conducts 4 test scenarios that result in a learning rate of 0.2, a multiplier learning rate of 0.4, a minimum learning rate of 0.001, and a training data of 60. The result of accuracy is 70%.